Development of a character instrument based on Al-Islam and kemuhammadiyahan values for muhammadiyah higher education students: a systematic literature review - Megawati Megawati; Dwi Sulisworo; Muhammad Sayuti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Character development in higher education faces increasing challenges due to rapid social change, digitalization, and growing expectations for graduates to demonstrate not only religious integrity but also social responsibility and leadership competencies. In Muhammadiyah Higher Education Institutions, Al-Islam and Kemuhammadiyahan (AIK) values serve as the core foundation of character education. However, existing learning approaches and measurement instruments tend to emphasize religiosity and have not yet adequately captured the multidimensional nature of student character development. In response to this issue, this study aims to develop a conceptual basis for AIK-based character education instruments through a systematic literature review. A total of 23 relevant studies were analyzed to synthesize AIK learning strategies, character dimensions and indicators, and methodological challenges in measuring AIK-based character development in higher education contexts. The synthesis reveals that effective AIK learning strategies such as direct instruction, habituation, role modeling, and value reflection contribute to multiple character dimensions, including religious spiritual, moral social, social engagement, leadership, and Muhammadiyah identity. The findings also highlight the importance of character indicators that integrate cognitive, affective, and psychomotor domains and are responsive to digital, multicultural, and prophetic values. This review identifies a significant gap in the availability of comprehensive, valid, and contextually grounded psychometric instruments for assessing AIK-based character development in higher education. By proposing an integrated conceptual framework, this study contributes theoretically to clarifying AIK-based character development and provides direction for future instrument development, assessment, and evaluation practices within Muhammadiyah Higher Education Institutions.